BENTUK DAN FUNGSI KESENIAN TRADISIONAL TONG-TONG PREK DESA JATIREJO KECAMATAN AMPELGADING KABUPATEN PEMALANG - ibrahim, manggih (Jurnal Seni Musik, 2014)
Traditional Art Ã¢â‚¬Å“Tong-Tong PrekÃ¢â‚¬Â of Desa Jatirejo Kecamatan Ampelgading Kabupaten Pemalang is the only one traditional art of tong-tong prek in Desa Jatirejo. Traditional Art Ã¢â‚¬Å“Tong-Tong PrekÃ¢â‚¬Â of Desa Jatirejo Kecamatan Ampelgading Kabupaten Pemalang can produce a unique music. The purpose of the music of Ã¢â‚¬Å“tong-tong prekÃ¢â‚¬Â actually to wake the people up in fasting month, but in that village the music of Ã¢â‚¬Å“tong-tong prekÃ¢â‚¬Â not only becomes a music to wake the people up, but also to be a show for the people. In the other town, it is also called Ã¢â‚¬Å“Thek-ThekÃ¢â‚¬Â or Ã¢â‚¬Å“Thong-Thong LekÃ¢â‚¬Â. The musics that produced in this traditional art are campursari tone with song lyrics that they produce by themselves. The themes of the songs are about islamic, peopleÃ¢â‚¬â„¢s lives, and also about neightborhood security system (siskamling). The objective of this research is to find the type and the function of Traditional Art Ã¢â‚¬Å“Tong-Tong PrekÃ¢â‚¬Â of Desa Jatirejo Kecamatan Ampelgading Kabupaten Pemalang.